Care and community reintegration of homeless people living with severe mental disorders: a community-based mental health programme in Maryland County, Liberia. Issue 1 (April 2020) - Cyrus, Garmai; Lusaka, Joseph; Yansine, Willis; Fannoh, Josiah; Wilson, Jesse; Coleman, Sarah; Houde, Amruta; Smith, Stephanie; Raviola, Giuseppe
Abstract: Background: The psychological impact of more than a decade of civil conflict and the Ebola outbreak has contributed to a mental health crisis in Liberia that is intensified by misconceptions, stigma, and discrimination surrounding mental disorders. Liberia faces severe shortages of mental health professionals and supplies to address the disease burden, with less than 1% of Liberians having access to appropriate mental health services. The global prevalence of mental disorders is 10% and between 25% and 31·5% in the homeless population. Here, we describe a community-based mental health programme integrated into primary care in Harper and Pleebo districts in Maryland County, Liberia, adapted to meet the needs of homeless patients living with severe mental health disorders. Methods: In 2016, Partners in Health Liberia (PIH Liberia) began engaging with community leaders such as town chiefs, religious leaders, and local government to provide information on mental health disorders and to understand the location of homeless patients in Maryland. Through continuous dialogue and engagement with local leaders, PIH Liberia began providing care to homeless patients with severe mental illness with community support. Supervised by psychiatric nurses, a community health worker (CHW) in each district performed daily follow-up with patients until clinical improvement was observed. During their visits, CHWs provided food and other social assistance, monitored side-effects of medication, observed medication administration, and ensured patients' personal hygiene. Once the condition of patients improved, CHWs helped patients reunite with their families, continued regular follow-up, and accompanied patients to the clinic as needed. Findings: Between 2016 and 2018, 96 homeless patients with severe mental illness were enrolled in the community-based mental health programme. After 3 years of implementation, 84 patients (88%) were reintegrated into the community; the remaining 12 are still homeless and remain supported by CHWs. With PIH's support, 20 reintegrated patients opened small businesses, four returned to school, and four became peer supporters and community advocates to reduce stigma and discrimination of other people living with mental disorders. To ensure adequate social support, PIH Liberia provided monthly food rations for 20 patients and built two houses for patients. Interpretation: Holistic community-based mental health programmes targeting homeless populations with both appropriate medical management and social support can significantly improve treatment outcomes and reintegration in the community. Funding: Partners in Health